Numerical Simulation of Different Splitter Angles of a Pelton Bucket to Increase the Power Generated by The Pelton Wheel - Sierra Del Rio, Jorge Andrés; Ruiz Sánchez, Alejandro (International Journal of Integrated Engineering, 2023)
The efficiency of a Pelton turbine depends mostly on its geometry. A design with suitable dimensions, offers higher generation of energy. However, some of these dimensions are underappreciated because of their low influence. Therefore, this study presents through a recompilation of data, the simulation was developed in ANSYS 19®. The importance of taking in count each parameter of the geometry of a Pelton bucket, analysing in this work the influence of the splitter angle in the force generated by a bucket. Nine geometries of a Pelton bucket are developed with splitter angles between 17 and 25°. The most suitable angle is determined, finding through the simulations that the geometry of 23° generates more force than other geometries. Simplifying the geometry and the mesh can generate faster results, however, exaggerating in the meshing process will affect the reliability of the obtained results.